ROS mediated high anti-bacterial efficacy of strain tolerant layered phase pure nano-calcium hydroxide. (August 2017) - Samanta, Aniruddha; Podder, Soumik; Ghosh, Chandan Kumar; Bhattacharya, Manjima; Ghosh, Jiten; Mallik, Awadesh Kumar; Dey, Arjun; Mukhopadhyay, Anoop Kumar
Abstract: The present work provides the first ever report on extraordinarily high antibacterial efficacy of phase pure micro-layered calcium hydroxide nanoparticles (LCHNPs) even under dark condition. The LCHNPs synthesized especially in aqueous medium by a simple, inexpensive method show adequate mechanical properties along with the presence of a unique strain tolerant behaviour. The LCHNPs are characterized by FTIR, Raman spectroscopy, XRD, Rietveld analysis, FE-SEM, TEM, TG-DTA, surface area, particle size distribution, zeta potential analysis and nanoindentation techniques. The LCHNPs have 98.1% phase pure hexagonal Ca(OH)2 as the major phase having micro-layered architecture made up of about 100–200 nm thick individual nano-layers. The nanomechanical properties e.g., nanohardness (H) and Young's modulus (E) of the LCHNPs are found to have a unique load independent behavior. The dielectric responses (e.g., dielectric constant and dielectric loss) and antibacterial properties are evaluated for such LCHNPs. Further, the LCHNPs show much better antibacterial potency against both gram-positive e.g., Staphylococcus aureus ( S. aureus) and gram-negative e.g., Pseudomonas putida ( P. putida ) bacteria even in dark especially, with the lowest ever reported MIC value (e.g., 1 μg ml −1 ) against the P. putida bacterial strain and exhibit ROS mediated antibacterial proficiency. Finally, such LCHNPs has almost 8–16% inhibition efficacy towards the development of biofilm of these microorganisms quantified by colorimetric detection process. So, such LCHNPs may find potential applications in the areas of healthcare industry and environmental engineering. Graphical abstract: Highlights: LCHNPs exhibited adequate mechano-chemical integrity. Its show better antibacterial efficacies against both S. aureus and P. putida bacteria. The lowest ever reported MIC value (e.g., 1 μg ml −1 ) against the P. putida bacteria. Thus proficient inhibition efficiency accounted for generation of ROS. Biofilm inhibition of P. putida and S. aureus was found to be 16% and 8% respectively.